Terorisme dan perang dalam al-quran - saleh, Nuralin (UIN Kiai Haji Achmad Siddiq Jember, 2024)
This essay was written to help people understand the prohibitions of the Koran and the dangers of terrorism and war by examining the meaning of these concepts in the holy verses of the Koran. The focus here is on the verses in the Koran that refer to terrorism and battle. This article was written using the literature study approach, which entails compiling a list of books, journals, and articles that address the topic at hand. An examination of the meanings of